CALCULATION RESERVOIR STRUCTURE ANALYSIS AND NEEDS OFWATER IN VILLAGE OF BUKIT PINANG DISTRICTS SAMARINDA ULU SAMARINDA - ASWIN, ELFIANSYAH (KURVA S JURNAL MAHASISWA, 2015)
Preparation of this paper aims to know how the steps in planning a network system needs clean water in an area. Areas of interest in the preparation of this essay in the Village Bukit Pinang District of Samarinda Ulu Kota Samarinda. In the preparation of this paper, there are two steps done. The first collects data last 5 years the number of people to analyze the needs of clean water. The method used to analyze the amount of clean water needs by using population projections for the next 20 years. After the clean water needs in mind, the next step of designing buildings supporting the clean water network system. Support buildings designed in the preparation of this paper that the reservoir. In the calculation of reservoir building structure using cross section.Â Â From the analysis of the needs of clean water in the village hill nut that is assuming for the next 20 years the importance of the need for water in the village of Bukit Pinang ie, 47.51 liters / second. So that the capacity of the reservoir is used to offset fluctuations pengguanaan clean water in the village of Bukit Pinang is 884.31 m3.Akan but in this paper the design of the structure of the reservoir in the view becomes a capacity 2100 m3. It is intended that the reservoir was built to serve all the needs of water in the city of Samarinda. uctures used in the reservoir is reinforcedÂ concrete.